FAKTOR-FAKTOR YANG MEMPENGARUHI KETEPATAN WAKTU PELAPORAN KEUANGAN PADA PERUSAHAAN YANG TERINDEKS DI INDEKS SAHAM SYARIAH INDONESIA - NILA PRATIWI; SIGIT SANJAYA (Maqdis: Jurnal Kajian Ekonomi Islam, 2017)
The theme of the article is "economy based on the principles of Islam". This research to analyze the factors influencing timeliness financial reporting in Indonesian Stock Exchange (IDX) period 2011 - 2015.Population of This Research is 359 companies listed in Indeks Saham Syariah Indonesia. Sample is determined by Slovin Formula, total sample is 190 companies, then sample is determined by purposive sample. Total sample in this research 50 companies. Data source is secondary data. Analysis data use descriptive statistic and logistic regression. Analysis data use Nagelkerke R Square to test framework conceptual, simultaneously test by using Omnibus Test Model Coefficient and hypothesis test by using significant test. Result of this research: profitability have not significant effect to timeliness financial reporting, firm size have not significant effect to timeliness financial reporting, liquidity have not significant effect to timeliness financial reporting.